1993
DOI: 10.5032/jae.1993.04046
|View full text |Cite
|
Sign up to set email alerts
|

Using The Innovation Adoption Diffusion Model To Target Educational Programming

Abstract: The adoption of new ideas and practices is affected by at least five factors: 1) the type of decision involved in adoption; 2) perceived attributes of the innovation; 3) communication channels used; 4) nature of the client system; and 5) the extent of the practitioner's effort (Lamble. 1984). A major function of extension practitioners is to facilitate the adoption of new ideas and practices or to influence the rate of diffusion and adoption of innovations by their clients. To enhance their effectiveness as ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 3 publications
0
7
0
1
Order By: Relevance
“…Extension educators and communicators should target the use of communication methods discussed in this study according to how producers use each method (Bouare & Bowen, 1990;Radhakrishna et al, 2003;Richardson & Mustian, 1994;Rollins, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Extension educators and communicators should target the use of communication methods discussed in this study according to how producers use each method (Bouare & Bowen, 1990;Radhakrishna et al, 2003;Richardson & Mustian, 1994;Rollins, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…A study by Rollins in 1993 confirmed that there are multiple information sources for farmers to use. found that newsletters (79%), manuals (68%), and magazines (68%) were used by high percentages of farmers to gain information about environmental issues.…”
Section: Introductionmentioning
confidence: 97%
“…The adoption-diffusion model provides a theory base for explaining how people adopt new practices, and most of the research has focused on determining the characteristics of the different adopter categories (Rogers, 1995). For example, a Pennsylvania study of farm operators found that 11% were late adopters, 37% were late majority, 34% were early majority, 18% were early adopters, and none were classified as innovators (Rollins, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Work shows that successful adoption of innovative conservation practices will be enhanced if awareness of the concerns, ideas, and varying perspectives of the target community are included in the design of extension processes [33, 34]. Research on adoption of innovative agriculture practices in other regions has found social aspects to be very significant to the adoption process [35, 36, 37, 38, 39].…”
Section: Introductionmentioning
confidence: 99%